Outer Retinal Layers’ Thickness Changes in relation to Age and Choroidal Thickness in Normal Eyes - Mona Kamal Abdellatif; Yasser Abdelmaguid Mohamed Elzankalony; Ahmed Abdelmonsef Abdelhamid Ebeid; Weam Mohamed Ebeid (Journal of Ophthalmology)
Purpose. To identify and correlate age-related changes in outer retinal layers’ thickness and choroidal thickness (CT) in the normal eyes using spectral-domain optical coherence tomography (SD-OCT) and to investigate factors affecting these changes. Study Design. Observational cross-sectional study. Subjects and Methods. We studied 125 healthy Egyptians between 20 and 79 years old. Patients were divided into 3 groups: group 1 (20–40 years), group 2 (40–60 years), and group 3 (>60 years). All patients had full ophthalmic examination. SD-OCT was done to measure the 9 ETDRS macular grid sectors of retinal pigment epithelium and photoreceptor outer segment (RPE-OS), outer nuclear layer and photoreceptor inner segment (ONL-IS), and choroidal thickness (CT) (by enhanced depth imaging). Results. RPE-OS was significantly thinner in group 3 than in the other 2 groups (central: P<0.001). Moreover, the 3 groups were significantly different from each other regarding the CT (central: P<0.001); significant thinning was noticed in the choroid with age. The 3 groups did not show significant difference concerning the ONL-IS thickness. RPE-OS and CT showed statistically significant negative correlation with age (central RPE-OS: r = −0 C.345, P<0.001, and central CT: r = −0.725, P<0.001) while ONL-IS showed statistically nonsignificant correlation with age (central ONL-IS: r = −0.08, P=0.376). Multiple regression analysis revealed that the most important determinant of central 1 mm RPE-OS thickness in this study was age (β = −0.087, P=0.010) rather than choroidal thinning (β = 0.001, P=0.879). Conclusion. RPE-OS layer thickness shows significant thinning with increasing age, and with decrease in CT, however, age is the most determinant factor of this thinning.